Produktion und Faktoreinsatz unter Transformationsbedingungen: Ökonometrische Analyse der Produktionstechnologie der ukrainischen Milchverarbeitungsindustrie; Production and Factor Input under Conditions of Transition: Econometric Analysis of the Production Technology of the Ukrainian Milk Processing Industry - Oleksandr Perekhozhuk; Michael Grings (German Journal of Agricultural Economics (GJAE), 2011)
– In this study estimation results of alternative production functions for the Ukrainian milk processing industry at the sectoral level are presented. Several special cases of a translog production function are estimated on the basis of a data set consisting of monthly time series for the period January 1996 to December 2003. The analysis focuses on key parameters of the production technology, such as the elasticity of scale, the elasticity of substitution of production factors and the rate of technical progress. The estimation results show that neoclassical production functions are less suited for the analysis than the unrestricted translog production function. Because of the special situation of the Ukrainian milk processing industry during the transition process, it can even be misleading to describe the production technology by a neoclassical production function. Thus, the marginal product of labour turns out to be negative, which is incompatible with neoclassical production theory. However, in view of the low capacity utilization this is not implausible. The estimation results with respect to the elasticity of scale cannot be interpreted unambiguously. The rate of technical progress is 2.7 % p.a. in the second half of the investigation period, while in the first half it is negative. The size of the Allen elasticities of substitution of production factors is calculated to be almost negligible.
Keywords: 330; Milchverarbeitung; Produktionstechnik; Agrarproduktion; Transformationsstaaten; Ukraine